Pengaruh Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien di Ruang Rawat Inap RSUD Menggala Kabupaten Tulang Bawang Provinsi Lampung - Nia Arita; Nur’aini Nur’aini; Ramadhani Syafitri Nasution; Juliandi Harahap; Endang Maryanti (STIKES Columbia Asia Medan, 2024)
Hospitals are a comprehensive part of social and media organizations whose function is to provide complete health services to the community, both curative and rehabilitative, hospital services reach family and environmental services. The aim of the research is to analyze the influence of health service quality on patient satisfaction in the inpatient room of Menggala Regional Hospital, Tulang Bawang Regency, Lampung Province. Analytical survey research design with a cross sectional design. The total population of patients treated from June 2022 to August 2022 in the Inpatient Room at Menggala Regional Hospital, Tulang Bawang Regency is 167 people. The number of samples was 62 people. The results of the chi square test research show that there is an influence of 8 variables, namely technical competence, human relations, effectiveness, efficiency, continuity, security, human relations and comfort, which have a p-value <α 0.05, meaning that technical competence, human relations, effectiveness, efficiency, continuity, safety, human relations and comfort influence patient satisfaction in the Menggala Hospital inpatient room. The results of the multiple logistic regression test are the most dominant comfort variable with an odds ratio (OR) of 18.455, meaning that it influences patient satisfaction 18 times. The conclusion is that the comfort variable is the dominant variable that has the most influence on patient satisfaction in the Menggala Hospital inpatient room. It is recommended for hospitals to adopt policies to increase patient comfort in treatment rooms in order to produce optimal satisfaction for patients.